Film Sang Kiai sebagai Media Komunikasi Dakwah Islam dalam Membentuk Kesadaran Nasionalisme Religius - Siti Rahma Harahap; Irma Suryani (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2026)
Film as a mass communication medium plays an important role in conveying the message of da'wah and national values ​​to the public. This study aims to analyze the film Sang Kiai as an Islamic communication medium in shaping religious nationalism awareness. The study uses a qualitative approach with a content analysis method of scenes, dialogues, characters, and visual symbols in the film Sang Kiai (2013). The results show that this film effectively conveys the message of da'wah through the example of ulama, narratives of struggle, and religious and national symbols. KH. Hasyim Asy'ari is represented as a da'wah communicator who integrates Islamic values ​​with the spirit of nationalism. Religious nationalism in the film is displayed through the concept of hubbul wathan minal iman, the struggle against colonialism, and the unity of the people in maintaining independence. In addition to being entertainment, Sang Kiai also functions as a da'wah medium and social education that can build awareness about the relationship between Islam and nationalism in the life of the nation and state.